Effect of perceptions and behaviour on access to and use of financial service: Evidence from South Africa - Samuel Kobina Annim; Thankom Arun; Philip Kostov (Institute for the Study of Labor (IZA), 2012)
This study investigates the effect of financial perception and behaviour on; (a) general accounts and services, (b) investment/savings and (c) insurance/assurance Using FinScope dataset from South Africa over the period 2003 to 2009,ordered probit, generalized ordered probit and pseudo panel micro-econometric techniques have been employed. Results based on all three estimations support the hypothesis that financial perception has a greater effect on the decision to access and use general accounts and services. The cross section and pooled models confirm the hypothesis that the effect of financial behaviour is greater than financial perception when making decisions on the take-up and use of investment financial services. It is also observed that the degree of responsiveness of financial perception on access to, and use of financial services decreases as the depth of usage deepens from basic to advance levels of financial products. In a policy context, targeting demand-side factors to increase access to and use of financial services should be financial type and level specific. Furthermore, the approach should be based on an understanding of the experiences of borrowers.
Keywords: O16; O17; G02; O55; 330; financial; perception; behaviour; general accounts; investment; insurance; South Africa; Finanzdienstleistung; Wahrnehmung; Bankgeschäft; Konsumentenverhalten; Südafrika